2007
DOI: 10.1063/1.2761502
|View full text |Cite
|
Sign up to set email alerts
|

Local surface potential distribution in oriented ferroelectric thin films

Abstract: Using Kelvin force microscopy, the authors have investigated the potential distribution on ferroelectric films. The local distribution of potential was observed on downward, prepoled areas. The polarity of the potential corresponds to the screen charge. It was found that the electrical properties of the grain boundary affect the potential distribution. Most of the grain boundaries show a lower potential than the area inside the grain. The authors identified certain regions at the grain boundary with a very low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…2,3,9 It is noted that the surfaces of the as-deposited films with the upward polarization as in the monodomain are screened by the negative screen charges being revealed as surface potential of 100-150 mV. As the positive voltage bias increases, the more negative charges, i.e., electrons, are injected and further accumulated as the extra screening charges.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…2,3,9 It is noted that the surfaces of the as-deposited films with the upward polarization as in the monodomain are screened by the negative screen charges being revealed as surface potential of 100-150 mV. As the positive voltage bias increases, the more negative charges, i.e., electrons, are injected and further accumulated as the extra screening charges.…”
mentioning
confidence: 98%
“…1 There have been few attempts to observe nanoscale screen charge behaviors on the ferroelectric surfaces. [2][3][4][5] Kalinin and Bonnell 5 discussed the relationship between surface potential polarity and polarization orientation in as-deposited ferroelectric surfaces. Chen et al 2 reported the surface potential dependence on the pulse voltages, duration, and overscreened state of the poled regions in the written ferroelectric domains of Pb͑Zr, Ti͒O 3 thin films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…KPFM was used to study the surface charges dynamics process by imaging surface screening charge distribution 10,11 . Figure 1e displays the KPFM image for the patterned area shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A clear understanding of the behavior of surface charges after poling is crucial to utilizing ferroelectricity at the nanometer scale. Despite much of the work on the study of the SP of the ferroelectric materials [8][9][10][11][12] , relatively little emphasis has been placed on the readout method by measuring the non-contact SP in a ferroelectric memory, simply because the SP contrast (DSP) between oppositely polarized domains decays and fails to be kept as a memory, which is mainly due to the evolution and recombination of the movable surface charges 7,8,11,13 around the domain walls. So far, the room-temperature stability of DSP has not been succeeded, so the high density memory based on this concept faces critical challenge.…”
mentioning
confidence: 99%